"Brand India" in Korea: A Case Study and Review of Nation Branding Research - Anand, Rahul (Indian Journal of Marketing, 2013)
The purpose of the study is to present a literature review on the nation brand concept and to examine "Brand-India" - its image, associations, and the effect of age and education on brand salience of Korean consumers. 100 respondents were interviewed about their association with India, Indian firms, and 'Made in India' products they wished to buy. ANOVA of the number of responses was done to analyze the effect of age and education of the respondents contributing to the brand awareness of India. It was observed that Indians were perceived to be friendly, kind, and good in maths by the Korean respondents. A majority of the respondents expressed a desire to purchase clothes that are 'Made-in-India,' followed by Food and IT products. The Tata Group was the most well known Indian firm in Korea, and the study found a significant effect of age and education in brand awareness of Indian companies. This case study adds to the study of 'Brand India' as well as to the study of nation branding and country image.